2008
DOI: 10.1253/circj.72.489
|View full text |Cite
|
Sign up to set email alerts
|

Impending Epidemic Future Projection of Heart Failure in Japan to the Year 2055

Abstract: eart failure (HF) is a major and growing public health problem in developed countries. 1 In the United States, approximately 5 million individuals have HF, and more than 550,000 new cases are diagnosed annually. 1 To our knowledge, only a few reports have focused on this issue in Japan. 2,3 The purpose of this study was to estimate the impact of population aging on the number of outpatients with left ventricular dysfunction (LVD) over the next 5 decades in Japan. All study participants provided informed consen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
172
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(188 citation statements)
references
References 2 publications
0
172
1
1
Order By: Relevance
“…The number of patients with HF is predicted to increase gradually along with the increasingly aging population 3. In order to manage patients with HF properly, including frequency of outpatient examination, doses of optimal medications, and indications for cardiac resynchronization therapy or ventricular assist device, risk classification is a high priority.…”
Section: Introductionmentioning
confidence: 99%
“…The number of patients with HF is predicted to increase gradually along with the increasingly aging population 3. In order to manage patients with HF properly, including frequency of outpatient examination, doses of optimal medications, and indications for cardiac resynchronization therapy or ventricular assist device, risk classification is a high priority.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several differences between Japan and other countries in both characteristics and management of ADHF, a comprehensive strategy for ADHF management ultimately should not differ significantly between Japan and other countries. Moreover, compared with other countries, Japan has experienced a marked increase in the ageing population, 30 and the incidence of new onset heart failure has also rapidly increased in recent years 2, 29. As the result of the increase in the ageing population, we are currently facing a worldwide heart failure pandemic, and the risk is particularly great in developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…The number of Japanese patients with heart failure was 979 000 in 2005 and is predicted to increase gradually as the population ages, reaching 1.3 million by 2030. 2 Moreover, the westernization of lifestyle and nutrition transition has facilitated the development of coronary artery disease and a higher proportion of ischaemic heart disease among heart failure patients 3, 4. Consequently, Japanese patients with heart failure have several unique clinical characteristics that might affect their prognosis including a high prevalence of preserved ejection fraction (HFpEF), multiple comorbidities, and lack of established treatment in elderly patients,5, 6, 7 and a longer length of hospital stay 4.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, it is anticipated that the incidence of left ventricular dysfunction will initially increase rapidly and then increase more slowly to reach a peak of 1.32 million patients by 2035, with the rapid phase of increase occurring by 2020. 1) To understand the nature of heart failure (HF), it is necessary to understand the relationship between the heart and other organs, such as the brain, lung, kidney, and liver. With respect to the relationship between the heart and kidney, for example, some reports have shown that exercise therapy correlates with improvements in renal function in patients with both cardiovascular disease and chronic kidney disease.…”
Section: Introductionmentioning
confidence: 99%